(untitled) (American Journal of Technology and Applied Sciences, 2026)
The article discusses the main algorithms of automated control of simulator training of ATC controllers. A methodology for organizing joint simulator training of flight crews and ATC specialists has been developed, based on mastering a set of competencies allocated for a set of exercises for the development of individual knowledge suitable for instrumental assessment and automation. Basic algorithms for the tasks of an automated modular simulator based on a semantic network have been developed with readjustment of the learning rate by changing the level of trainees’ load on the automated simulator system for the training of flight crews and ATC specialists. It is shown that the use of automated modular simulators makes it possible to improve flight safety, as well as to increase the speed and efficiency of training military pilots and ATC specialists.